Precision implant placement: A novel approach using dynamic navigation system-guided alveolar ridge splitting - M. Satyanarayana Raju; Sruthima N. V. S. Gottumukkala; Koyya Sesha Sai Rakshitha; M. A. K. V. Raju (The Journal of Indian Prosthodontic Society)
Conventional alveolar ridge splitting (ARS) technique involves a significant risk which may prove problematic. This case report presents the first documented application of dynamic navigation system (DNS)-guided ARS, demonstrating a precise approach to implant placement in a challenging anatomical scenario. A 37-year-old partially edentulous patient presented with missing mandibular posterior teeth. Clinical examination revealed a deficient alveolar ridge. Cone-beam computed tomography evaluation showed a Siebert’s Class I resorbed ridge with 2.5 mm width and bone density ranging from 870 to 1040 Hounsfield Units in the #46 and #47 regions. Creating and designing three-dimensional virtual guide slits and implant planning using DNS were done in patient with insufficient bone width in the mandibular molar region. Piezoelectric ARS, osteotomy preparation with implant placement was done. 0.70 and 0.26 mm deviations at #46 and 0.50 and 0.01 mm deviations at #47 were observed at implant entry and implant apex, respectively. The angular deviations were optimal. ARS using real-time navigation appears to be an efficient and promising technique.